Effects of Different Taping Techniques in Individuals with Myofascial Pain Syndrome with a Trigger Point in the Trapezius Muscle: A Sham-controlled Randomized Study - Kubra KARDES; Pinar VAN DER VEER; Yunus Emre TUTUNEKEN; Hale Nur AYKAC; Esra ARSLAN; Aysenur AKSOY; Yasemin BURAN CIRAK (Medeniyet Medical Journal)
Objective: This study aimed to compare the effects of three different kinesio taping (KT) techniques in individuals with myofascial pain syndrome (MPS) who have a trigger point in the trapezius muscle. Methods: The individuals included in our study were randomly divided into four groups: Group 1: Functional correlation technique, group 2: Fascia correlation technique, group 3: Star taping technique (STT), and group 4: Sham group. The visual analog scale was used to assess pain, cervical joint range of motion (ROM) with a universal goniometer, grip strength with a hand dynamometer, number of active trigger points by palpation, pressure-pain threshold with an algometer, quality of life with the Nottingham Health Profile and functional level with the Neck Disability index were evaluated before and after treatment. Results: There was no difference between the groups in terms of demographic data and pre-treatment outcome measures (p>0.05). There was a significant difference in the pain score between the groups after treatment (p<0.05). A statistically significant difference was found in the cervical flexion ROM of all groups after treatment (p<0.05). In pairwise comparisons, these differences were found due to group 3 (p<0.05). Conclusions: The three KT techniques are effective in reducing pain, increasing ROM, reducing the number of active trigger points, and increasing grip strength. Among these techniques, STT was found to be more effective in reducing pain and increasing cervical flexion ROM. KT is a method that can be used in the clinic for patients with MPS.